INTERNATIONAL TRADE IN SERVICES BY THE UKRAINIAN ENTERPRISES: THE STATISTICAL REVIEW AND POSSIBLE WAYS OF ITS DEVELOPMENT - Дячек, В. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
This article is dedicated to investigation of the current status of international trade in services by the Ukrainian enterprises and the desirable trends of its development. It was conducted statistical analysis of the data of the Government Committee of Statistic of Ukraine, calculated the figures of the development, structural analysis and found the trends of its development. As a result of this investigation indentified the desirable trends of development of international trade in services.